The significance of troponin T and CK-MB release in coronary artery bypass surgery - Mohiti, Javad (Springer India, 2004)
Measurement of cardiac markers is an index of care standard in the assessment and diagnosis of cardiovascualr disease. Two of the major cardiac markers are Creatine Kinase isoenzyme CK-MB and Troponin T, which are extensively used in the diagnosis of heart disease. The release of Troponin T and creatine kinase isoenzyme (CK-MB) was investigated in 50 coronary artery bypass surgery patients. Measurement of plasma samples was carried out at five different time points, namely before surgery, 1,6,12,24 hours after surgery. The results indicated that CK-MB level were increased by a factor more than four times compared with the upper limit of baseline (befor surgery). Troponin T concentration showed more than six fold over the upper limit of baseline (before surgert) at 1,6,12,24 hours after surgery. In order to assess the significance of the length of the surgical procedure on the release of Troponin T and CK-MB, the surgery patient were divided into two groups according to the length of the surgical procedure: group I was selected on the basis that the surgical procedure they underwent lasted above 90 minutes and group II with a surgical procedure below 90 minutes. Both Troponin T and CK-MB showed a significant increase in-group I compared to group II. To investigate the likelihood that this effect is party due to myocardial infarction during surgery, the patients were divided into two groups: Group A with some sings of myocardial infarction on Q wave of ECG and group B without any change. The results showed approximately a two-fold increase of these markers in-group A compared to group B. Since these markers reach into blood following damage to myocardial their increase in patients with time course surgery of more than 90 minutes and those with a probability of MI during operation, indicating that these patient fall into a high risk group of repeat (MI) after surgery.